Li-Bi-Se semiconductor thin films: technology, structure and electrophysical properties - Bilozertseva, V.I.; Khlyap, H.M.; Shkumbatyuk, P.S.; Dyakonenko, N.L.; Mamaluy, A.O.; Gaman, D.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The results of structural investigations and electric field-induced properties of thin (40–100 nm) Li-Bi-Se films grown on glass substrates by means of the resistive evaporation technique are reported. The experimental investigations of microstructure and phase composition of thin films by transmission electron microscopy (TEM) and electron diffraction methods are carried out. Тhe experimental current-voltage dependences and transport of charge carriers are discussed.